(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2019)
The present investigation is a contribution of the Oficina de la Cronista Municipal del Municipio Palavecino, Lara state, to the understanding of the historical process of consolidation of this locality since its original conformation of colonial "sitio" to the current city of Cabudare, capital of the municipality. It addresses its political, territorial and administrative changes, since it began as a "sitio", and its transformation process into an ecclesiastical parish, civil parish, “cantón”, department, district, municipality, and even, at certain times, capital of estado Lara, Venezuela. It also reviews the creation of the parishes that currently make up the municipio Palavecino, and its dismemberment for the creation of the municipio Simon Planas. This history is reconstructed, taking into account geographical, economic, social, political and demographic aspects, for an integral understanding, as a synthesis history. A hermeneutics of bibliographic, hemerography and documentary sources was carried out.